PENINDAKAN PELANGGARAN PEMILIHAN UMUM OLEH BADAN PENGAWAS PEMILU KOTA SAMARINDA - Dinny Wirawan Pratiwie; Tumbur Ompu Sunggu; Gabriel Satw Satw (Yuriska: Jurnal Ilmiah Hukum, 2024)
Based on the Constitution of the Republic of Indonesia, the implementation of general elections is a reflection of the application of the concept of democracy which is emphasized in Article 1 paragraph (2) which reads "sovereignty is in the hands of the people and is implemented according to the Constitution", which is further confirmed in Article 22 E paragraph (1) which states that "general elections are held directly, publicly, freely and secretly". During elections, the possibility of violations or unlawful acts does not rule out the possibility. Bawaslu is an ad hoc institution formed during the first stage of the election, namely at the voter registration stage which begins and is disbanded after the candidates selected in the election have been inaugurated. An election supervisory committee (Panwaslu) was formed to supervise the election stages, receive complaints, and handle cases of administrative violations and criminal election violations. The approach method used is a doctrinal approach, using primary legal materials and secondary legal materials, which are then analyzed qualitatively and described. Forms of violations included in supervision by Bawaslu consist of Election Administration Violations, Election Crime Violations, Violations of the Code of Ethics. The form of action against election violations is basically that the City Bawaslu provides recommendations according to the level of the violation.